Estudo de procedimentos analíticos para determinação de Cr(III) e Cr(VI) em amostras sólidas - Matos, Wladiana Oliveira (2006)
The legislation is evolving towards the establishment of restrictions to the concentration of Cr(VI), the most toxic redox form of chromium, in solid materials. This aspect has stimulated the development of sample preparation procedures for redox speciation analysis of chromium in solid samples. In the work here described it was studied procedures for Cr(VI) extraction in solid samples using alkaline solutions. Molecular absorption spectrophotometry based on 1,5 - diphenylcarbazide as chromogenic reagent was used for the determination of Cr(VI). The quantification of Cr(III) was carried out by the subtraction of the total chromium concentration and the concentration of Cr(VI). The samples employed were: soils, cements, cementrelated materials, nutritional complements and metallic components. The extractor solution composed by 0.10 mol L-1 Na2CO3 presented good performance for solid samples. Tests of stability of Cr(VI) indicated that reduction of Cr(VI) to Cr(III) did not occur in the adopted extraction conditions, even in the presence of significant amounts of Cr(III). The diphenylcarbazide method presents good sensitivity for the determination of Cr(VI) in extracts, however the presence of organic matter in the soil samples caused interferences. The total chromium concentrations were determined using either FAAS or ICP OES after complete decomposition of the samples. Sample preparation procedure for total chromium determination was implemented according to the type of sample. Cement samples and cement-related materials were decomposed by fusion. On the other hand, all the other samples were microwave-assisted digested using high pressure vessels. The main limitation of the studied procedures is the evaluation of accuracy because of the lack of standard reference materials.